Feedback on SMS reminders to encourage adherence among patients taking antipsychotic medication: a cross-sectional survey nested within a randomised trial. Issue 11 (9th November 2015) - Kannisto, Kati Anneli; Adams, Clive E; Koivunen, Marita; Katajisto, Jouko; Välimäki, Maritta
Abstract : Objectives: To explore feedback on tailored SMS reminders to encourage medication adherence and outpatient treatment among patients taking antipsychotic medication, and associations related to the feedback. Design: A cross-sectional survey nested within a nationwide randomised clinical trial ("Mobile.Net" ISRCTN27704027 ). Setting: Psychiatric outpatient care in Finland. Participants: Between September 2012 and December 2013, 403 of 558 adults with antipsychotic medication responded after 12 months of SMS intervention. Main outcome measure: Feedback was gathered with a structured questionnaire based on Technology Acceptance Model theory. Data were analysed by Pearson's χ 2 test, binary logistic regression and stepwise multiple regression analyses. Results: Almost all participants (98%) found the SMS reminders easy to use and 87% felt that the SMS did not cause harm. About three-quarters (72%) were satisfied with the SMS received, and 61% found it useful. Divorced people were particularly prone to find SMS reminders useful (χ 2 =13.17, df=6, p=0.04), and people seeking employment were more often 'fully satisfied' with the SMS compared with other groups (χ 2 =10.82, df=4, p=0.029). People who were older at first contact with psychiatric services were more often 'fully satisfied' than younger groups (OR=1.02, 95% CI 1.01 to 1.04, p=0.007). Conclusions: The feedback of patients taking antipsychotic medication on SMS services was generally positive. Overall, people were quite satisfied despite considerable variation in their sociodemographic background and illness history. Our results endorse that the use of simple easy-to-use existing technology, such as mobile phones and SMS, is acceptable in psychiatric outpatient services. Moreover, people using psychiatric outpatient services are able to use this technology. This acceptable and accessible technology can be easily tailored to each patient's needs and could be customised to the needs of the isolated or jobless. This is an area in which much careful evaluation is needed.